(untitled) (Journal of Science and Technology, 2016)
The paper presents a method for decomposing interconnected power systems into subsystems. Each subsystem is associated with mechanical modes which represent intermachine oscillations within it. The resulting decomposition is shown to give correct grouping of generating units for the development of dynamic equivalents for dynamic studies. The capability of the method is illustrated by a 10-machine 39-bus power system.